Viability of On-Orbit Servicing Spacecraft to Prolong the Operational Life of Satellites. Issue 2 (June 2022) - Hatty, Isabella
Abstract: This research paper is an extensive literature review and data analysis on the viability of on-orbit servicing (OOS) spacecraft to prolong the operational life of satellites. A systematic analysis of the Union of Concerned Scientists (UCS) Satellite Database found that Sentinel 1A and 1B orbit at approximately the same height as Landsat 7 ( ∼ 700 km) and have a collective propellant mass (MProp ) of 308 kg which is less than Landsat 7′s 544 kg. The On-orbit Servicing, Assembly and Manufacturing (OSAM) 1 spacecraft has the capacity to refuel both Sentinels as an alternative option to Landsat 7. For OSAM 1 to refuel Landsat 7, it is $261.91 M cheaper than replacement and the more economically viable and sustainable option. OSAM 1 will mitigate the immediate problem of space debris. However, a new model of standardized cooperative satellites with external plug-in interfaces could facilitate both planned and unplanned upgrades, modifications and repairs for changing missions and technology updates for the future.